Buckling of a tilted line of confined hard spheres - Hutzler, Stefan; Weaire, Denis (My University, 2022)
A linear chain of hard spheres confined in a transverse harmonic potential is unstable and buckles, if tilted beyond some critical angle. We examine this symmetry breaking using a computational model that was previously applied to buckling under compression. Results are presented in a bifurcation diagram (in terms of energy as a function of tilt), including both stable and unstable equilibrium states. The key results are consistent with experiments using metal spheres resting in a cylinder.
PUBLISHED
Keywords: buckling; bifurcations; symmetry breaking; chains of particles; Nanoscience & Materials